2021
DOI: 10.3390/ijms22126533
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Haptoglobin and Its Proteoforms as Glioblastoma Markers

Abstract: Haptoglobin (Hp) is a blood plasma glycoprotein that plays a critical role in tissue protection and the prevention of oxidative damage. Haptoglobin is an acute-phase protein, its concentration in plasma changes in pathology, and the test for its concentration is part of normal clinical practice. Haptoglobin is a conservative protein and is the subject of research as a potential biomarker of many diseases, including malignant neoplasms. The Human Hp gene is polymorphic and controls the synthesis of three major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
2
17
0
1
Order By: Relevance
“…A recent report found that SCX regulated Twist1 and Snai1 expression in the epithelialto-mesenchymal transition (45). HP was regarding as a molecular biomarker in non-small cell lung cancer and glioblastoma (46,47). We also verified the high accuracy of the RCIP4 risk model both in the TCGA-ccRCC and JAPAN-KIRC database.…”
Section: Discussionsupporting
confidence: 72%
“…A recent report found that SCX regulated Twist1 and Snai1 expression in the epithelialto-mesenchymal transition (45). HP was regarding as a molecular biomarker in non-small cell lung cancer and glioblastoma (46,47). We also verified the high accuracy of the RCIP4 risk model both in the TCGA-ccRCC and JAPAN-KIRC database.…”
Section: Discussionsupporting
confidence: 72%
“…Three major phenotypes according to gene polymorphisms (Hp1-1, Hp2-1, and Hp2-2), unprocessed precursors (proHp1 and proHp2), and unusually glycosylated Hp (especially fucosylated Hp) have been reported and they play diverse roles in inflammation, diabetic vascular disease, angiogenesis, and malignant tumors [ 19 , 20 , 24 ]. The plasma Hp level, Hp expression in tumor cells, and Hp fucosylation are reportedly related to cancer development and have been suggested to be candidate biomarkers of various cancers including HCC, colorectal cancer, pancreatic cancer, and glioblastoma [ 20 , 33 , 34 ]. In addition, a preliminary report showed an association of tissue Hp expression and the EMT in buccal cancer [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrate that HP expressions are higher in the serum of patients with liver cancer, lung cancer, ovarian cancer, or other cancers than in the serum of healthy subjects. Furthermore, HP expressions combined with other serum markers, would be of reference value to the early diagnosis of relevant cancers and of some guiding significance in terms of treatment and prognosis ( Naryzhny et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%